Sequestering CO2 by Mineralization into Useful Nesquehonite-Based Products - Glasser, Fredrik Paul; Jauffret, Guillaume; Morrison, Jennie; Galvez-Martos, Jose-Luis; Patterson, Naomi; Imbabi, Mohammed Salah-Eldin (Frontiers in Energy Research, 2016)
The precipitation of magnesium hydroxy-carbonate hydrates has been suggested as a route to sequester CO2 into solids. We report the development of self-cementing compositions based on nesquehonite, MgCO3⋅3H2O, that are made from CO2-containing gas streams, the CO2 being separated from other gases by its high solubility in alkaline water, while magnesium is typically provided by waste desalination brines. Precipitation conditions are adjusted to optimize the formation of nesquehonite and the crystalline solid can readily be washed free of chloride. Products can be prepared to achieve self-cementation following two routes: (i) thermal activation of the nesquehonite then rehydration of the precursor or (ii) direct curing of a slurry of nesquehonite. The products thus obtained contain ~30 wt% CO2 and could form the basis for a new generation of lightweight, thermally insulating boards, blocks, and panels, with sufficient strength for general construction.